Working on an Historical Dictionary: The Swedish Academy Dictionary Project - Stille, Per; Wendt, Bo-A. (Lexikos, 2001)
Abstract: The Swedish Academy Dictionary is one of the world’s largest dictionary projects. Work on it was started in 1884 and it will be completed by 2017. The dictionary describes the written standard language of Swedish from the beginning of the sixteenth century until the present. It is therefore both historical and contemporary. In this article the background and scope of this huge project are presented with a description of what an entry contains, and how it is constructed. The problems of describing a language simultaneously from both an historical and a contemporary aspect are also dealt with. Keywords: CHRONOLOGY, CONTEMPORARY DICTIONARY, DIACHRONY, ENTRY, HISTORICAL DICTIONARY, LANGUAGE HISTORY, LEXICOGRAPHIC DESCRIPTION, STANDARD LANGUAGE, SYNCHRONY. Opsomming: Om aan ’n historiese woordeboek te werk: Die woordeboekprojekvan die Sweedse Akademie. Die woordeboek van die Sweedse Akademie iseen van die wêreld se grootste woordeboekprojekte. In 1884 is begin om daaraan te werk en dit salteen 2017 voltooi wees. Die woordeboek beskryf die geskrewe standaardtaal van Sweeds vanaf diebegin van die sestiende eeu tot die hede. Dit is gevolglik sowel histories as kontemporêr. In hierdieartikel word die agtergrond en omvang van hierdie enorme projek aangebied met ’n beskrywingvan wat ’n inskrywing bevat, en hoe dit saamgestel is. Die probleme om ’n taal gelyktydig vansowel ’n historiese as ’n hedendaagse gesigspunt te beskryf, word ook behandel. Sleutelwoorde: CHRONOLOGIE, HEDENDAAGSE WOORDEBOEK, DIACHRONIE, INSKRYWING,HISTORIESE WOORDEBOEK, TAALGESKIEDENIS, LEKSIKOGRAFIESE BESKRYWING,STANDAARDTAAL, SINCHRONIE.